Undulator beamline optimization with integrated chicanes for X‐ray free‐electron‐laser facilities. (31st May 2016) - Prat, Eduard; Calvi, Marco; Ganter, Romain; Reiche, Sven; Schietinger, Thomas; Schmidt, Thomas
Abstract : An optimization of the undulator layout of X‐ray free‐electron laser facilities based on installing small chicanes in the space between the undulator modules is presented. The chicanes allow the saturation length to be reduced, the brightness to be increased and very short and high‐power pulses to be generated. Abstract : An optimization of the undulator layout of X‐ray free‐electron‐laser (FEL) facilities based on placing small chicanes between the undulator modules is presented. The installation of magnetic chicanes offers the following benefits with respect to state‐of‐the‐art FEL facilities: reduction of the required undulator length to achieve FEL saturation, improvement of the longitudinal coherence of the FEL pulses, and the ability to produce shorter FEL pulses with higher power levels. Numerical simulations performed for the soft X‐ray beamline of the SwissFEL facility show that optimizing the advantages of the layout requires shorter undulator modules than the standard ones. This proposal allows a very compact undulator beamline that produces fully coherent FEL pulses and it makes possible new kinds of experiments that require very short and high‐power FEL pulses.